Notary Investigation in Making Copies of CV's Deed Establishment Which Different Numbers in Minuta - Mauliawati Alifah (Sultan Agung Notary Law Review, 2021)
CV deed whose minute deed number is different from the copy of the deed. The existence of a Notary who is summoned and examined by the Police is related to the tasks carried out by a Notary, namely: making a copy of the CV's deed of establishment which turns out to be a different number from the minutes of the deed. Meanwhile, the notary concerned does not believe that the copy of the deed has a different number with the minutes of the deed. Notaries have the responsibility in terms of discrepancies between the Copies of the Deed and the Minutes of the Deed, which have been regulated both in the Act and in the Notary Code of Ethics. This study uses normative juridical. Normative juridical research examines the factual implementation or implementation of positive legal provisions (laws) and contracts in each particular legal event. The results of this study are 1) The role of the investigator against the Notary who makes a copy of the deed, Investigators, Public Prosecutors, and Judges are only allowed to take photocopies of the minutes of the deed and/or letters attached to the minutes of the deed or the protocol of the notary in the notary's storage, as long as for the interest of the judicial process and has obtained the approval of the Notary Honorary Council; 2) Efforts that can be made by a notary in the event of a typo contained in the minutes of the deed whose copy has been issued are basically casuistic in nature, for example the Deed of Establishment of a Limited Liability Company (CV), there is a typo.